Assessment of a novel bleaching agent formula containing 35% hydrogen peroxide and titanium tetrafluoride: an in vitro study - Lins,Rodrigo Barros Esteves (2021)
Abstract: This study developed experimental gels containing titanium tetrafluoride (TiF4) combined with commercial 35% hydrogen peroxide (HP), and evaluated bleaching efficacy and pH of the gels, and mineral content and morphology of enamel submitted to these treatments. In phase-1, different stock gels mixed with TiF4 were combined with HP. In phase-2, the selected gels were tested on enamel/dentin specimens (n=8): HP; HP and Natrosol+TiF4 (HPnT); HP and Natrosol+Chemygel+TiF4 (HPncT); HP and Aristoflex+TiF4 (HPaT). Bleaching was performed in four sessions (3x15min-application/session). Color (CIEL*a*b*) and whiteness index (WID) were measured after each session, whereas whiteness index differences (ΔWID), color alteration (CIELab–ΔE, CIEDE2000-ΔE00), enamel morphology and pH, at end of bleaching therapy. The change in Knoop microhardness (ΔKHN) was compared before and after bleaching. Data were analyzed by two-way repeated measures ANOVA and Bonferroni (CIEL*, a*, b*), one-way ANOVA and Tukey (ΔWID, ΔE, ΔE00), and LSD (ΔKHN) tests (α=5%). SEM and pH measurements were submitted to descriptive analysis. No differences were observed in lightness (L*) or WID among the groups (p > 0.05), but HP exhibited lower b* values (p<0.05), higher ΔWID than HPnT, and the highest ΔE among the groups (p < 0.05). No differences in ΔE00 were observed between HP and HPncT (p > 0.05), and HPncT showed higher ΔKHN than HP (p < 0.05). HP presented pH values closer to neutral (6.9), whereas experimental agents showed acidic pH values (2.3–3.9). No morphological changes were observed in HP or HPncT groups. HPncT was able to bleach the enamel and maintain enamel microhardness and surface integrity, even at low pH.